2023
DOI: 10.18632/aging.204462
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of a novel circadian clock-related prognostic signature and its role in immune function and response to molecular targeted therapy in pancreatic cancer

Abstract: Background: Pancreatic ductal adenocarcinoma (PADA) represents a devastating type of pancreatic cancer with high mortality. Defining a prognostic gene signature that can stratify patients with different risk will benefit cancer treatment strategies. Methods: Gene expression profiles of PADA patients were acquired from the Cancer Genome Atlas and Gene Expression Omnibus, including GSE62452 and GSE28735. Differential expression analysis was carried out using the package edgeR in R. Intro-tumor immune infiltrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…IL-27 signaling in Tregs plays a crucial role for the proteinogenic properties of Tregs by upregulating CD39 [ 36 ]. Dabrafenib and Linsitinib have been tentatively applied to pancreatic ductal adenocarcinoma with poor prognosis after conventional cytotoxic chemotherapy [ 37 , 38 ]. We found DE-ILRGs related drugs like Dabrafenib and Linsitinib from the CellMiner database, which can provide a new chance for treatment of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…IL-27 signaling in Tregs plays a crucial role for the proteinogenic properties of Tregs by upregulating CD39 [ 36 ]. Dabrafenib and Linsitinib have been tentatively applied to pancreatic ductal adenocarcinoma with poor prognosis after conventional cytotoxic chemotherapy [ 37 , 38 ]. We found DE-ILRGs related drugs like Dabrafenib and Linsitinib from the CellMiner database, which can provide a new chance for treatment of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The stress-induced protein kinase CK1 delta (CSNK1D) lies in the long arm of chromosome 17 (17q25.3) in humans, encoding CK1δ, a member of the CK1 family ( Graves et al, 1993 ). Increasing studies have demonstrated that the dysregulation and activity of CK1δ expression are not only found in various cancers but also in different neurological diseases including AD ( Zhu et al, 2022 ; Jin et al, 2023 ). Hence CSNK1D is expected to be a promising treatment target for AD.…”
Section: Discussionmentioning
confidence: 99%
“…A separate gene expression profile analysis stratified PDAC patients based on genetic risk profiles to utilize targeted molecular therapies. KLF10 was one of thirteen genes involved in the low-risk prognostic signature, relatively defined as improved prognosis and increased sensitivity to cancer treatment [192]. The high-risk cohort, devoid of low-risk genes, had lower CD8 T/B cells and a higher neutrophil count associated with PDAC proliferation and metastasis [192].…”
Section: Klfs As Potential Biomarkersmentioning
confidence: 99%
“…KLF10 was one of thirteen genes involved in the low-risk prognostic signature, relatively defined as improved prognosis and increased sensitivity to cancer treatment [192]. The high-risk cohort, devoid of low-risk genes, had lower CD8 T/B cells and a higher neutrophil count associated with PDAC proliferation and metastasis [192]. When high KLF10 expression was combined with chemoradiotherapy (CRT) treatment, patients had significantly better recurrence-free and overall survival times, indicating KLF10 positively influenced the benefits of adjuvant CRT [193].…”
Section: Klfs As Potential Biomarkersmentioning
confidence: 99%